10 years of the International Treaty on Business and Human Rights negotiation: the importance and challenges of regulating the transnational character of business - Carneiro Roland, Manoela (Homa Publica - Revista Internacional de Derechos Humanos y Empresas, 2025)
This paper looks back at the process of negotiating the International Treaty on Business and Human Rights, which emblematically reached its tenth year with the adoption of Resolution 26/9 of the United Nations Human Rights Council in 2014. In this sense, we focus on the central point, still under discussion, which concerns the need to concentrate the scope of the international instrument on transnational corporations (TNCs), but, on the other hand, to understand that the meaning attributed to these entities is more eminently related to the nature of the transnational activity, in fact, its transnational character, the definition of which must be improved, and not to the legal nature of the corporations. We argue that the choice of proposals on the subject for the International Treaty should follow the logic adopted in internationally recognized spaces for defending human rights, as the Human Rights Council should be, and not for safeguarding business interests. In this way, the negotiation process should respond to the demands of those affected, who continue to have their rights violated, without an adequate international response. This article was written for the Transnational Institute (TNI) (https://www.tni.org/en) as a product of research on the 10th anniversary of Resolution 26/9 (A/HRC/RES/26/9) for the Global Campaign to Reclaim Peoples Sovereignty, Dismantle Corporate Power and Stop Impunity, submitted in December 2024.